Understanding factors affecting youth involvement of Public Universities in sports tourism in Malaysia: push and pull factors analysis - Tong Hui Wen; Nurul Syahirah Ahmad Zaidi; Nurul Yusairah Mohamad Zain; Satheasilan Ganesan (2016)
Youth participation in sport tourism in Malaysia has been increasing over the years. This research is aimed to understand the factors that affecting youth involvement in sports tourism in Malaysia. The factors that were chosen was pull factors and push factors. The pull factors are identified as destination attribute, safety and security, attraction, and faculties; while the push factors are self-expressiveness, relaxation, time, and financial. Based on the sample of youth population in selected public universities (n=384), the study reveals the significant of push and pull factors among youth in participating sport tourism. The results show that the push factors have a higher influence on youth compared to pull factors.